Detection of Lard and Interesterified Lard as Adulterants in Some Vegetable Oils and Selected Fried Food Products - Marikkar, J. M. Mohammed Nazrim (2004)
Mixing of pork and lard in food systems is an important food safety issue. In view of the religious restrictions and risks associated with consumption of pork and lard, there is a growing need for lard detection methods in food systems. In fact, it is very essential to distinguish lard adulteration from other common animal fat adulterations so that misleading conclusions could be avoided in analytical determinations. Therefore, in this project we attempted to explore the potential of analytical techniques such as gas liquid chromatography (GLC), high performance liquid chromatography (HPLC), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) spectroscopy for the detection of lard contamination in some vegetable oils and some fried food products. In the initial stage, compositional and thermal profiles of genuine lard (GLD) were compared with those of beef tallow (BT), mutton tallow (MT) and chicken fat (CF).The GLC studies showed that percent palmitic acid enrichment factor [PAEF (%)] for GLD was unusually high when compared to other animal fats. According to HPLC, triacylglycerol (TAG) profile of GLD was quite different from that of BT/MT but seemed to have a close resemblance to that of CF. However, the TAG peak ratio LOO/SPO of GLD was found to be a useful parameter to differentiate GLD from CF. In the DSC analysis, GLD was found to have cooling and heating profiles which were completely different from those of other animal fats and therefore easy to identify. Similarly, compositional and thermal characteristics of genuine lard (GLD) were also compared with chemically interesterified lard (CLD) and enzymatcally interesterified lard (ELD) in order to find common merits between them. Even though GLD and interesterified lard (GLD/ELD) were similar in overall fatty acid composition, they differed in their sn-2 positional distribution of fatty acids. Particularly, PAEF was no longer a common characteristics between GLD and CLD. Drastic differences were also noted with respect to their TAG and DSC thermal profiles. With this background study, investigations were scheduled to determine the presence of lard as an adulterant in the admixtures of palm oil (PO), palm kernel oil (PKO), and canola oil (CLO) using four major analytical techniques, namely GLC, HPLC, DSC, and FTIR spectroscopy. In these studies, special attention was paid to discriminate lard adulteration from other animal fat adulterations when they were present in admixtures. Investigations conducted with GLC showed that it was very difficult to distinguish lard adulteration from other animal fats adulterations based on the overall FA data.However, more promising results were obtained for FA compositional changes in the 2-position of TAG isolated for each adulterated sample of vegetable oil. Additionally, mathematical equations obtained by simple regression analysis could be used for quantification of lard content in admixtures. HPLC was the next analytical technique used for detection of lard. HPLC analyses were performed to monitor the TAG compositional changes in the oil samples before and after adulteration. The results showed that qualitative determination of lard contamination in PKO was possible by visual comparison of HPLC profiles of PKO with those adulterated with different animal fats whereas this approach was not found useful for detection of lard in PO and CLO. However, by subjecting liquid chromatographic data into multivariate statistical analysis, it was shown that distinguishable grouping for lard-contaminated samples could be possible for all the three oils investigated in this study. Investigations conducted with DSC showed that it was very difficult to locate an adulteration peak corresponding to lard for PKO adulterated series since the changes caused by GLD and CF were similar. In PO, DSC heating thermogram did not provide any positive indication for lard detection whereas DSC cooling profiles of adulterated PO samples showed an adulteration peak corresponding to lard in the low temperature region. In CLO, adulteration peak corresponding to GLD was found to emerge in the higher temperature region of the DSC heating thermogram. FTIR spectroscopy was the last technique employed to detect lard in vegetable oils. According to the results, FTIR/ATR technique seemed to be very useful analytical tool for detection of AF adulterations in general since it clearly highlights the deviations taking place in different spectral regions of vegetable oils. However, using this technique it was not possible to pinpoint any characteristic features peculiar to lard occurring in all three vegetable oils since the changes cased by all AF in many regions of the spectra were similar. Therefore, FTIR/ATR may not be a suitable technique to detect the presence of lard in vegetable oils. In the last part of the project means of identifying lard contamination in fried food products was investigated by employing GLC, HPLC and DSC techniques. Results showed that PAEF calculated from GLC analysis of fatty acid methyl esters seems to be a useful parameter in determining lard contamination in all four fried products. Using TAG profiling by HPLC, it was possible to detect lard in fried- chicken and fried-tempeh while DSC cooling and heating traces were found to be useful for lard detection in fried-tempeh, fried-chicken and fried-beef products.